Bibliometric and Visual Analysis of Vascular Calcification Research - Dong, Qian; Liang, Qingchun; Chen, Ying; Li, Jinhe; Lu, Lihe; Huang, Xiongqing; Zhou, Qin (Frontiers in Pharmacology, 2021)
Background: Extensive studies related to vascular calcification (VC) have been conducted in the recent years. However, no bibliometric analysis has investigated this field systematically so far. Our study aimed to determine the hotspots and frontiers of VC research in the past decade. Methods: Literatures on VC research were acquired from the Web of Science Core Collection (WoSCC). Bibliometric and visual analysis were implemented by CiteSpace, VOSviewer and Microsoft Excel software. Results: 8238 English articles of VC research published from 2011 to 2020 were obtained. In the past decade, the annual publications and citations had shown a significant growth trend, especially from 2018 to 2020. The most productive country, institution, journal and author were the USA, the University of California System, Plos One, and Budoff MJ, respectively. The highest-cited country, journal and author were the USA, Journal of the American College of Cardiology, Floege J, respectively. “Vascular calcification,” “atherosclerosis,” “chronic kidney disease (CKD),” and “cardiovascular disease (CVD)” were the prime keywords. The burst keywords “revascularization,” “calciprotein particle,” “microrna,” and “microcalcification” were speculated to be the research frontiers. Conclusion: The main research hotspots in VC field were the molecular mechanisms and the prognosis of VC in CKD or CVD patients. In addition, endovascular therapy and the development of new drugs targeting on signal pathways for VC will become the foci of future research. Moreover, ncRNAs related to the diagnosis and treatment of VC have great research prospects.